2010
DOI: 10.1098/rsbl.2010.0411
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative assessment of the diet of European eel larvae in the Sargasso Sea resolved by DNA barcoding

Abstract: European eels ( Anguilla anguilla ) undertake spawning migrations of more than 5000 km from continental Europe and North Africa to frontal zones in the Sargasso Sea. Subsequently, the larval offspring are advected by large-scale eastward ocean currents towards continental waters. However, the Sargasso Sea is oligotrophic, with generally low plankton biomass, and the feeding biology of eel larvae has so far remained a mystery, hampering understanding of this peculiar life history. DNA ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
74
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(80 citation statements)
references
References 19 publications
6
74
0
Order By: Relevance
“…A feeding ecology based on consuming marine snow can explain the observations of the DNA barcoding study of leptocephalus food contents [8] and of ciliates being consumed [7] because marine snow comprises detritus-like materials from all types of marine organisms that aggregate together, and thus these species or their tissue fragments could be present in the material ingested by leptocephali. Direct observations of the food contents of various species of leptocephali have consistently shown material that appears to be amorphous marine snow or discarded appendicularian houses and zooplankton faecal pellets [3][4][5] (see the electronic supplementary material, figure S3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A feeding ecology based on consuming marine snow can explain the observations of the DNA barcoding study of leptocephalus food contents [8] and of ciliates being consumed [7] because marine snow comprises detritus-like materials from all types of marine organisms that aggregate together, and thus these species or their tissue fragments could be present in the material ingested by leptocephali. Direct observations of the food contents of various species of leptocephali have consistently shown material that appears to be amorphous marine snow or discarded appendicularian houses and zooplankton faecal pellets [3][4][5] (see the electronic supplementary material, figure S3).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, marine snow and appendicularian houses contain micro-organisms such as bacteria and protozoans and colonizing animals such as ciliates, copepodid stages, and anthozoan, mollusc and polychaete larvae [6,22]. The aggregation of organismal materials in POM probably explains the presence of the DNA sequences detected in small European eel larvae [8], although leptocephali may also sometimes directly consume small organisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As part of this study, we performed molecular analysis of gut content of bivalve larvae following the bottle incubations, and where there were sufficient larvae, on the gut content of larvae taken directly from the field. Recent studies have used DNA-based techniques for dietary analysis including PCR amplification of 18S genes from the gut content of zooplankton (Nejstgaard et al 2003;Troedsson et al 2007;Nejstgaard et al 2008;Troedsson et al 2009;Durbin et al 2012), including meroplanktonic larvae (Maloy et al 2009;Riemann et al 2010;Fileman et al 2014). If the gut content of the predator can first be removed to reduce coamplification of host DNA, then general or universal primers designed to conserved regions (Holland et al 1991) targeting the 18S gene can be used.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, there is motivation for improved understanding of ecological processes that supports the early life of the Atlantic eels in this region (Munk et al 2010). Early studies suggested that the prey of eel larvae includes larvacean houses and zooplankton faecal pellets (Mochioka & Iwamizu 1996), but recent data suggest that the diet encompasses a wide range of plankton organisms, including gelatineous zooplankton and copepods (Riemann et al 2010).…”
Section: Introductionmentioning
confidence: 99%